Single by chance, mothers by choice : how women are choosing parenthood without marriage and creating the new American family - Hertz, Rosanna (New York ; Oxford : Oxford University Press, 2006)
How do women juggle earning a paycheck with parenting? What creative ways have women devised to shore up these families? How do they incorporate men into their child-centered families? This book provides answers to all these questions, offering an account of how middle class women have managed to make single parenthood work for them.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Families -- United States; Single mothers -- United States; Middle class women -- United States